The impact of tumor burden at the initial hepatectomy on the recurrence-to-death survival after repeat surgical resection/radiofrequency ablation: a retrospective study - Youwei Wu (BMC Surgery, 2022)
Abstract Background Previous studies have reported the surgical resection (SR) and radiofrequency ablation (RFA) could achieve comparable recurrence-to-death survival (RTDS). However, the impact of primary tumor burden on RTDS of patients with recurrent hepatocellular carcinoma (HCC) following SR or RFA has not been clarified. Methods From January 2009 to March 2015, 171 patients who underwent initial hepatectomy and second curative treatments in West China Hospital were retrospectively analyzed. Survival analysis was performed by the Kaplan–Meier method. Risk factors were identified using the Cox proportional hazard model. Results At initial hepatectomy, 96 patients (56.1%) were diagnosed with HCC within the Milan criteria (MC), and 75 patients (43.9%) were HCC beyond the MC. The clinicopathological features and re-treatment methods of recurrent HCC were similar between patients with primary HCC within or beyond the MC. Patients with primary HCC within the MC had longer recurrence time (31.4 ± 24.2 months vs. 20.2 ± 16 months, P < 0.001). The 1- and 3- year RTDS within and beyond the MC group were 88.8%, 57.6% and 79.0%, 46.3%, respectively (P = 0.093). In multivariate analysis, the recurrence time, tumor size and AFP > 400 ng/mL at the time of recurrence were associated with RTDS. Conclusions The primary tumor burden had no impact on RTDS, but had an impact on recurrence time. The recurrence time had an impact on RTDS and might be a good index to reflect the biology of recurrent HCC.